“I’m a Man, I’m a Nurse”: Breaking Strong Gender Stereotype towards Evocative Personal Narrative” - Dwi Rosita Sari (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Gender stereotypes are indicated as basic understandings why the femininity and masculinity take a crucial portion towards Indonesian higher educational majors and occupational choices. The formation of gender-based occupation stereotypes is that there is an assumption that to be successful in doing certain profession, one must have feminine or masculine qualities, depending on the type of job. In different case, the participant tries to break out those assumption by choosing profession. This study aims to reveal how personal narrative led someone to break general gender-based occupation stereotypes in Indonesia. The research method is qualitative. The participant was one male nurse through semi-structured interview. The result shows that specific plot of story life giving huge influence towards someone’s professional choices.